Staurogyne beddomei (Acanthaceae), a new record for Thailand - Choopan, Thiamhathai; Sungkaew, Sarawood; Toolman, Nopparut; Suddee, Somran (Thai Forest Bulletin (Botany), 2020)
Staurogyne beddomei, a species known previously only from Myanmar, is newly recorded for Thailand. A description, photographs and conservation status are provided - the species is considered to be of Least Concern.